IMPROVEMENT OF THERAPY FOR PATIENTS WITH LOCALIZED SCLERODERMA - Al-Omary, O.M.; Mahdebura, A.V.; М. С. Трет’яков; Alrabadi, M.M.; Smadi, D.M.; Aldheisat, A.A.; Abbas, R.T. (World of Medicine and Biology, 2025)
Localized scleroderma is a chronic multifactorial autoimmune disease affecting the skin and subcutaneous tissue. The aim of this study was to compare the clinical efficacy of two complex treatment regimens in patients with localized scleroderma combined with Lyme borreliosis. The study compared two regimens: one based on benzylpenicillin and the other on doxycycline hydrochloride 100 mg twice daily in 45 patients aged 20 to 64 years. Clinical manifestations, lesion activity using the modified Localized Scleroderma Skin Severity Index, and serum levels of pro-inflammatory interleukin-6 and anti-inflammatory interleukin-10 were evaluated before and 30 days after treatment. The results demonstrated a significantly greater reduction in skin lesion activity and pro-inflammatory interleukin-6 levels, alongside an increase in anti-inflammatory interleukin-10 in the doxycycline-treated group compared to benzylpenicillin. These results suggest that doxycycline hydrochloride offers superior clinical and immunological benefits in patients with localized scleroderma associated with Lyme borreliosis.
Keywords: localized scleroderma; Lyme-borreliosis; cytokines; benzylpenicillin; doxycycline hydrochloride